Nonlinear thermomechanical buckling of sandwich FGM oblique stiffened plates with nonlinear effect of elastic foundation. (October 2022) - Dong, Dang Thuy; Nam, Vu Hoai; Trung, Nguyen Thoi; Phuong, Nguyen Thi; Hung, Vu Tho
In this article, the nonlinear thermomechanical buckling behaviors of sandwich functionally graded plates subjected to an axial compression and external pressure are analytically analyzed resting on nonlinear elastic foundation. Assuming that the plates are reinforced by oblique stiffeners and rested on nonlinear elastic foundation. The formulations are established using the higher-order shear deformation theory taking into account the geometrical nonlinearity of von Kármán. The Lekhnitskii's smeared stiffener technique is developed for shear deformable oblique stiffener system using the coordinate transformation technique with both mechanical and thermal terms. The Galerkin method is utilized to obtain the nonlinear algebraically equation system, then, solve it to determine the explicit expressions of critical buckling loads and postbuckling load–deflection curves. Numerical results show the effects of temperature, nonlinear elastic foundation, stiffeners, and material and geometrical properties on nonlinear behaviors of plates.